Geographical origin of guarana seeds from untargeted UHPLC-MS and chemometrics analysis - Nunomura, Sergio Massayoshi; Nunomura, Rita de Cássia Saraiva; Muniz, Magno Perêa; Salles, Rita Cynara de Oliveira (Food Chemistry, 2022)
Guarana is one of the most popular functional foods in the Amazon and widely used in the world. This work aimed to study the chemical composition of guarana produced by the main producing states and try to associate their geographical origin. We report an untargeted metabolomic analytical method performed by UHPLC-ESI-IT-MS and multivariate analysis (chemometrics) of guarana seeds, which was able to separate the samples according to their geographical origin. Previously, full chromatogram range was analyzed, and it could be observed that the two main compounds, catechin and epicatechin, have introduced large data variance in PCA analysis not related to the geographical origin of samples. After exclusion of the corresponding peaks, it was possible to obtain three main clusters corresponding to samples from Amazonas, Bahia and Mato Grosso. Thirteen dimers and trimers of procyanidins type A and B were identified by PCA and UHPLC-ESI-Q-TOF-MS/MS, as chemical markers of geographic origin. © 2021
Keywords: Chemometrics; Fingerprint